DESAIN SISTEM AKUNTANSI PENJUALAN KREDIT DAN PEMBELIAN KREDIT PADA PD. BINTANG SAMUDERA PERKASA DI YOGYAKARTA - Supriono Supriono (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2017)
Teaches accounting system accounting information processing systems, since the data is recorded in a document through a variety of power-sharing system of the organization, financial data are processed in a variety of accounting records to the information presented in the financial statements. This study is intended to contribute to the Company Trade (PD) Bintang Samudera Perkasa, which is ditributor Isano PVC pipe, fittings, box gutters, hoses, gutters carpet, water faucets and others. Researchers will contribute about credit sales accounting system and accounting system of credit purchases. So that the company can properly record accounting transactions, it is necessary to be prepared a variety of recording procedures and support facilities. Transactions that occur in huge numbers in the company and can involve nearly every part of the company. Each transaction has its own characteristics, for example, there is associated with the receipt of cash, there are expenses associated with cash, there are related to the transfer of goods (both from within the company to the outside or vice versa), there are external parties involved, and there are many more. Because it has different characteristics, each transaction must be recorded in different ways. To set up accounting procedures vary, the required accounting systems. Key words: accounting system of credit sales and credit purchases accounting system in PD Bintang Samudera Perkasa